MENJEMBATANI KETERASINGAN: INTERVENSI PSIKOSOSIAL BERBASIS KOMUNITAS (CBPSS) SEBAGAI UPAYA PEMULIHAN HOLISTIK BAGI PENGUNGSI (REFUGEE) AFGHANISTAN PASCAKONFLIK - Chrysan Gomargana; Helsa Helsa; Christina Claudia; Caroline Mathilda V. Bolang (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The lives of Afghan refugees in Indonesia as a transit country are marked by limited access to basic rights and heightened psychosocial vulnerability. Prolonged conflict in their homeland, coupled with the uncertainty of their legal status in transit, has led to psychological difficulties such as trauma, anxiety, and social alienation. This program responds to these conditions by designing a Community-Based Psychosocial Support (CBPSS) intervention targeting two primary groups: refugee children and adults. For children, the intervention consisted of play-based emotional regulation and self-expression activities, while adults underwent PHQ-9 screening and individual counseling with professional psychologists. A total of 58 participants were involved, including 28 children and 30 adults. The findings indicate that this approach enhanced children’s ability to express emotions and provided a safe space for adults to process emotional burdens. Techniques such as infinity breathing and progressive muscle relaxation were valued by participants for being simple yet effective. Community feedback reflected an overall improvement in collective psychosocial well-being, with ratings of 4/5 for program communication and 5/5 for its perceived benefits. These results suggest that CBPSS can serve as an adaptive, impactful, and sustainable model for refugee psychosocial recovery.